Проблема Ляпунова и синтез оптимальных систем управления - Задорожный, В.Ф. (Кибернетика и системный анализ, 2010)
Прямий (перший) метод Ляпунова — ефективний спосіб аналізу та синтезу динамічних систем керування. Центральним місцем методу є побудова функції Ляпунова. Для нелінійної динамічної системи це проблематично. Розглянуто спосіб побудови функцій Ляпунова як розв’язку рівняння Гамільтона–Якобі, яке зводиться до інтегрального рівняння типу Фредгольма. The direct (first) Lyapunov method is an efficient method for analysis and synthesis of dynamic control systems. The construction of the Lyapunov function occupies the central place in this method, which is a challenge for nonlinear dynamical systems. A general mathematical scheme of construction of the Lyapunov function as a solution of the Hamilton-Jacoby equation is considered that is reduced to an equation of the type of the Fredholm equation.